2018
DOI: 10.3390/act7030037
|View full text |Cite
|
Sign up to set email alerts
|

A Bouc–Wen Model-Based Compensation of the Frequency-Dependent Hysteresis of a Piezoelectric Actuator Exhibiting Odd Harmonic Oscillation

Abstract: This paper proposes an enhancement of the Bouc-Wen hysteresis model to capture the frequency-dependent hysteretic behavior of a thin bimorph-type piezoelectric actuator which also exhibits odd harmonic oscillation (OHO) at specific input frequencies. The odd harmonic repetitive controller has recently been proposed to compensate for the hysteresis, and attenuates the OHO of the piezoelectric actuator for which the hysteresis nonlinearity is regarded as a disturbance. This paper proposes an alternate treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Micky et al [19] established a compensator based on the Bouc-Wen model and the inverse multiplicative structure, completely removing the hysteresis of a unimorph cantilever in bench top test. Fumitake et al [20] used the Bouc-Wen model to model the hysteresis behavior of a thin bimorph-type piezoelectric actuator. A compensator was built based on this Bouc-Wen model and it exhibited good performance at a wide range of frequencies from 1 Hz to 50 Hz in experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Micky et al [19] established a compensator based on the Bouc-Wen model and the inverse multiplicative structure, completely removing the hysteresis of a unimorph cantilever in bench top test. Fumitake et al [20] used the Bouc-Wen model to model the hysteresis behavior of a thin bimorph-type piezoelectric actuator. A compensator was built based on this Bouc-Wen model and it exhibited good performance at a wide range of frequencies from 1 Hz to 50 Hz in experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, experts adopt various types of intelligent algorithms to identify the parameters of this model. For example, Rakotondrabe et al [13] proposed a method to identify the model parameters by using nonlinear filtering system; Charalampakis et al [14] proposed an improved particle swarm optimization algorithm to identify the model parameters; Fujii et al [15]. used the least square algorithm to identify the parameters of the improved model.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative and intensively studied approaches in the literature include the usage of phenomenological hysteresis models [8]. Examples include the Prandtl-Ishlinskii (PI) model [9], the Preisach model [10], the play and stop models [11,12], the Bouc-Wen model [13], and the Duhem model [14]. These phenomenological models are able to capture hysteretic behaviors accurately.…”
Section: Introductionmentioning
confidence: 99%
“…They regarded the odd harmonic component of the response as a disturbance and synthesized a repetitive controller for its attenuation. We previously proposed an enhanced Bouc-Wen model for capturing odd harmonic oscillation induced by a pure sinusoidal input at some driving frequency and proposed a corresponding compensator [13] based on the direct inverse multiplication proposed by Rakotondrabe [18]. Regarding the interleaved hysteresis, Alatawneh and Pillay [19] recently showed that interleaved hysteresis could be captured by the Preisach model by relaxing certain constraints in its distribution function.…”
Section: Introductionmentioning
confidence: 99%